2016
DOI: 10.3390/ijerph13020162
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Effect of Gene-Gene and Gene-Environment Interactions on the Risk of Prostate Cancer in Chinese Men

Abstract: Prostate cancer (PCa) is a multifactorial disease involving complex genetic and environmental factors interactions. Gene-gene and gene-environment interactions associated with PCa in Chinese men are less studied. We explored the association between 36 SNPs and PCa in 574 subjects from northern China. Body mass index (BMI), smoking, and alcohol consumption were determined through self-administered questionnaires in 134 PCa patients. Then gene-gene and gene-environment interactions among the PCa-associated SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…reported the association of six variants with PCa and their cumulative effect (32). This relationship suggested that men who carried any combination of 1, 2, or >3 risky genotypes had a gradually increased PCa risk.…”
Section: Discussionmentioning
confidence: 97%
“…reported the association of six variants with PCa and their cumulative effect (32). This relationship suggested that men who carried any combination of 1, 2, or >3 risky genotypes had a gradually increased PCa risk.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the interaction between the increased risk of prostate cancer and SNP variation of rs 1447295 was observed by several studies. 17,21 In other disease settings, some studies also found that the T allele of 8q24 rs10090154C>T was involved in the development of colorectal organ tumorigenesis. 30,31 They found that the T allele remained the important predictor in the development of tumorigenesis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we included a total of 16 papers in our meta-analysis. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We outline the flowchart of included papers in Figure 1, and the baseline characteristics are provided in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Although the incidence of prostate cancer in China is lower than that in western developed countries, the number of patients with prostate cancer is huge because of the large population base and increasing age 14. Radical prostatectomy is commonly used in the treatment of early prostate cancer, and patients usually have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%